PENGARUH STRUKTUR KEPEMILIKAN DAN KARAKTERISTIK DEWAN KOMISARIS TERHADAP PENGUNGKAPAN SUKARELA PADA PERUSAHAAN DI INDONESIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Aniroh, Sulung (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to obtain empirical evidence about the influence of ownership structure and board characteristics on voluntary disclosure in the annual reports of existing companies in Indonesia Stock Exchange (ISX) in 2010 and 2011. Ownership structure is characterized by managerial ownership, blockholder ownership and government ownership, and board characteristic is characteristic by independent directors, size of directors and skill of directos. Control variabels is leverage, firm size and profitabilitas. The population of this study is all companies listed in Indonesia Stock Exchange in 2010 and 2010. The total sample was 130 companies, with two years of observations. So the total sample who checked is 260. Data analysis was performed with the classical assumption and hypothesis testing using linear regression. The results of this study indicate that the factor of government ownership, size of directors, leverage and firm size significantly influence the voluntary disclosure. Meanwhile, managerial ownership, blockholder ownership, independent directors, skill of director, and profitabilitas has no significant impact on voluntary disclosure. Keywords: Voluntary disclosure, managerial ownership, blockholder ownership, government ownership, independent directors, size of directors and skill of directos.